Distribution and evolution of H1N1 influenza A viruses with adamantanes‐resistant mutations worldwide from 1918 to 2019. Issue 6 (1st December 2020) - He, Weijun; Zhang, Weixu; Yan, Huixin; Xu, Hefeng; Xie, Yuan; Wu, Qizhong; Wang, Chengmin; Dong, Guoying
Abstract: H1N1 influenza is a kind of acute respiratory infectious disease that has a high socioeconomic and medical burden each year around the world. In the past decades, H1N1 influenza viruses have exhibited high resistance to adamantanes, which has become a serious issue. To understand the up‐to‐date distribution and evolution of H1N1 influenza viruses with adamantanes‐resistant mutations, we conducted a deep analysis of 15875 M2 protein and 8351 MP nucleotides sequences. Results of the distribution analyses showed that 77.32% of H1N1 influenza viruses harbored‐resistance mutations of which 73.52% were S31N, And the mutant variants mainly appeared in North America and Europe and H1N1 influenza viruses with S31N mutation became the circulating strains since 2009 all over the world. In addition, 80.65% of human H1N1 influenza viruses and 74.61% of swine H1N1 influenza viruses exhibited adamantanes resistance, while the frequency was only 1.86% in avian H1N1 influenza viruses. Studies from evolutionary analyses indicated that the avian‐origin swine H1N1 influenza viruses replaced the classical human H1N1 influenza viruses and became the circulating strains after 2009; The interspecies transmission among avian, swine, and human strains over the past 20 years contributed to the 2009 swine influenza pandemic. Results of our study clearly clarify the historical drug resistance level of H1N1 influenza viruses around the world and demonstrated the evolution of adamantanes‐resistant mutations in H1N1 influenza viruses. Our findings emphasize the necessity for monitoring the adamantanes susceptibility of H1N1 influenza viruses and draw attention to analyses of the evolution of drug‐resistant H1N1 influenza variants.